MODERNIZATION OF THE ENERGY INDUSTRY AS A MAJOR FACTOR IN THE TRANSITION TO A GREEN ECONOMY (International Journal of Innovative Technologies in Economy, 2020)
The article gives basic concepts about a relatively new economic model of the "green" economy, considers the reasons for modernization of the energy industry as a factor in the transition to a low-carbon economy, shows the pressing problem of environmental pollution due to the use of traditional energy sources and the need to transition to renewable energy sources (RES).